Breathing across ages: a systematic review on challenges and components of transitional care for young people with asthma - Antonino, Luna; Van Hoorenbeeck, Kim; van Olmen, Josefien; Vanharen, Yaël; Janssens, Natwarin; Verhulst, Stijn; Goossens, Eva (Frontiers in Pediatrics, 2024)
Introduction: Asthma is a chronic condition that affects millions of adolescents and young adults (AYA) worldwide. The transition from pediatric to adult care presents unique challenges for this population, affecting their self-management, quality of life and overall health outcomes. This systematic review aims to consolidate the available evidence on challenges encountered by AYA with asthma during the transition period from child to AYA and on the key elements of transitional care for AYAs with asthma including the outcomes achieved, ultimately enhancing outcomes.Methodology: A systematic literature search was performed in PubMed, Embase, Medline, Scopus, and Web of Science from their inception to October 2, 2023, to provide an overview of currently available literature. Primary quantitative and qualitative studies, published in peer-reviewed journals that focused on AYA with a confirmed diagnosis of asthma were considered if they focused on challenges encountered by AYA with asthma during the transition process and/or components of transitional care and their outcomes assessed.Results: A total of 855 studies were initially identified and 6 articles were included in this systematic literature review. Several challenges experienced by AYA with asthma were identified including maintaining medication adherence, the need to take responsibility and being involved, understanding their condition and its severity, feeling left out of the care system, and experiencing a lack of engagement. The identified transitional care components included a standardized form for medical data transmission, a joint consultation and to offer several longer consultations.Several international guidelines for asthma care recommend implementing transition programs in the care for AYA with asthma. Such transition programs should include a comprehensive and individualized approach addressing several challenges faced, to ensure optimal outcomes posttransition. However, to date, data on effective components of transitional care facilitating good outcomes were found to be limited. This systematic review underscores the need for larger studies evaluating the effect of the components of transition programs.